Assembly and Comparative Analysis of Complete Mitochondrial Genome Sequence of Endangered Medicinal Plant Trichopus zeylanicus - Biju Vadakkemukadiyil Chellappan; P. R. Shidhi; Anu Sasi; Rashid Ismael Hag Ibrahim; Hamad Abu Zahra (Current Issues in Molecular Biology)
Plant mitochondrial genomes exhibit extensive size variability and structural complexity. Here, we report the complete mitochondrial genome of Trichopus zeylanicus, an endemic medicinal plant from the Western Ghats. The mitochondrial genome was assembled using a combination of Illumina short-read and PacBio long-read sequencing technologies, followed by extensive annotation and comparative analysis. The circular mitogenome spans 709,127 bp with a GC content of 46%, encoding 32 protein-coding genes, 17 tRNAs, and three rRNAs. Comparative analysis with other monocot mitochondrial genomes revealed conserved gene clusters but also significant lineage-specific rearrangements. Despite genome size similarities, T. zeylanicus displayed marked divergence in gene order, suggesting that genome size does not necessarily correlate with structural conservation. The genome contains 6.7% chloroplast-derived sequences and 324 predicted RNA-editing sites, predominantly in the first and second codon positions. Phylogenetic analysis based on mitochondrial genes placed T. zeylanicus as a distinct lineage within Dioscoreales, supporting its evolutionary uniqueness. This work provides the first mitogenomic resource for Dioscoreales and advances our understanding of mitochondrial diversity and evolution in monocots.